CIRI – CIRI POLA AGROSILVOPASTURA: STUDI KASUS DI DESA SUMARAYAR KECAMATAN LANGOWAN TIMUR - Mega Masyita Gusti; Semuel P. Ratag; Euis F.S. Pangemanan (Universitas Sam Ratulangi, 2022)
Abstract Agrosilvopasture is one part of the agroforestry system that can be offered as a land management system to overcome problems, among others, food availability, land ownership area, decreased soil fertility. The agrosilvopasture in question is a combination of woody annual plant components with agricultural crops (seasonal) and at the same time livestock on the same land. Sumarayar village is located in East Langowan District, Minahasa Regency, North Sulawesi Province. According to the Head of Sumarayar Village, the mayority of the people of Sumarayar Village are farmers and some of them are herding livestock on thesome land. This study aims to identify the agrosilvopasture pattern applied in Sumarayar Village, East Langowan District and identify the advantages and disadvantages of the applied agrosilvopasture pattern. This study uses a survey method by means of interviews and field observations. The results of this study indicate that the agrosilvopasture pattern in the village of Sumarayar grows annual woody plants as land boundaries and food crop barriers. The advantage of applying the agrosilvopasture pattern is to get maximum results with the presence of trees, food crops and livestock on the same land because income increases while the drawback is that it is difficult to measure productivity. Agricultural economists are accustomed to regular farming patterns, while in agroforestry this is not the case, there are various types of trees and shrubs whose economic value is not clear. Keywords: Agrosilvopasture, Sumarayar Village, East Langowan District